Peningkatan Hasil Belajar Alqur’an Hadist Melalui Metode Tahsin (Membaca) Pada Siswa Kelas XI MAS Jam’iyah Mahmudiyah Tanjung Pura - Erwin Syahputra (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to improve the ability to memorize the Qur'an of grade VII MTsS Jam'iyah Mahmudiyah students through the Role Playing method. The research uses a classroom action approach (Classroom Action Research) with two cycles, each cycle includes the stages of planning, implementation, observation, and reflection. In the pre-cycle, only 31% of students achieved completeness with KKM 75. After the application of the Role Playing method in cycle I, the completeness increased to 71%. In cycle II, the percentage of completion increased significantly to 91%. These results show that the Role Playing method is effective in improving students' ability to memorize the Qur'an, increase their active participation, and motivation to learn.